Pengaruh Media Smart Box Untuk Meningkatkan Pengetahuan Kesehatan Gigi Dan Mulut Dalam Mencegah Karies Gigi Pada Siswa Kelas V SD N Menteng 03 Pagi - Nurrochman, Aditya; Setyawati, Baby Prabowo; Hasanudin, Afif Afandy; Marelda, Amellea Firkintan (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2025)
Introduction: According to WHO, the average caries rate in children aged 6-12 years is very high, reaching 8.43. Children aged six years have a dmft of more than 6, reaching 67.3%, this is included in the category of early childhood dental caries. Based on the 2018 Basic Health Research survey (RISKESDAS), the prevalence of caries is still at 93%. Research Objective: to determine the effect of smart box media to increase knowledge of dental and oral health in preventing caries in class V students at SDN Menteng 03 Pagi. Research Method: the research design used was a pre-experiment with pre-test and post-test design. The sample in this study amounted to 58 respondents. Data analysis for this study used univariate tests and bivariate tests using the Kolmogorov-Smirnov and Wilcoxon tests. Research Results: Statistical tests show that there is an increase between the results of the pre-test and post-test scores, which is indicated by the asymp.sig value of 0.000 on the knowledge variable, meaning that the variable is <0.05, so it can be concluded that Ha is accepted. Conclusion: there is an influence of smart box media to increase knowledge of dental and oral health in preventing caries in fifth grade students at SDN Menteng 03 Pagi.